The Book of Samuel and its response to monarchy - Kipfer, Sara; Hutton, Jeremy M.; Hunziker-Rodewald, Regine; Naumann, Thomas; Klein, Johannes (Beiträge zur Wissenschaft vom Alten und Neuen Testament, 2021)
"Power comprises one of the key topics of the book of Samuel. This theme encompasses tribal contentions, power differentials between religious authorities and kings, fathers and sons, men and women. The articles assembled here explore Israel's search for political identity and Samuel's critique of monarchy, the book's constructions of power and powerlessness, and the editors' and early audiences' postmonarchic reflections. Historical and social-scientific approaches to the book of Samuel find ancient Near Eastern parallels for the political organization of Israel and describe the social conditions under authoritarian regimes. Redactional approaches examine the diachronic development of Samuel's varying perceptions of monarchy, from that institution's inception through its entrenchment in Israelite and Judahite society, until it underwent a sudden, cataclysmic failure. And literary and theological approaches advocate for contemporary reconsideration and application of the book's more noble principles."